The Influence of Literacy Skills on Improving Students Reading Interest in Indonesia Language Learning: A Quantitative Studi of 5th Grade Elementary Students - Nasution, Nirwansyah; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
This study examines the influence of literacy skills on the improvement of reading interest among fifth-grade students in Indonesian language learning at SD Negeri 135 Barbaran. The background indicates that students' literacy skills still need improvement. Initial observations and interviews with fifth-grade teachers confirmed low student reading interest due to a lack of reading habits outside lessons, exposure to monotonous reading materials, and limited facilities. Therefore, this research aims to provide concrete solutions through curriculum-integrated literacy development. A quantitative approach with an ex post facto method was employed. The study population comprised all 34 fifth-grade students of SD Negeri 135 Barbaran, who were included as a full sample using purposive sampling. Data were collected through questionnaires (reading interest) and tests (literacy skills). The instruments were validated (r-count > 0.3494) and reliable (Cronbach's Alpha 0.952). Data analysis included descriptive statistics, classical assumption tests (normality Sig. 0.200 ≥ 0.05; linearity Sig. 0.367 ≥ 0.05), and simple linear regression hypothesis testing. Descriptive data showed that students' literacy skills were predominantly in the "Very High" category (41%), followed by "Moderate" (32%) and "High" (27%). Students' reading interest was predominantly in the "Very High" category (59%), followed by "High" (35%) and "Moderate" (6%). The simple linear regression equation Y=58.694+0.194X indicated a positive influence: an increase in literacy skills would lead to an increase in reading interest. Although the regression's significance value was 0.457 (not significant at the 0.05 level), theoretically and based on consistent previous research findings, a positive influence between literacy skills and reading interest persists. Literacy skills contributed 1.7% to students' reading interest, while the remaining 98.3% was influenced by other factors such as individual interest, motivation, and environment. In conclusion, there is an influence of literacy skills on the improvement of reading interest among fifth-grade students of SD Negeri 135 Barbaran.